Increasing cycling for transportation through mentorship programs. (October 2019) - Kearns, Michelle; Ledsham, Trudy; Savan, Beth; Scott, James
Highlights: Cycling mentorship programs were effective in increasing cycling for transportation. Cycling increased for shopping, work and school trips. Participants increased cycling in suburban as well as more central areas. Participants increased their willingness to spend on a bicycle and accessories. Abstract: Policy statements and planning documents of many North American municipalities recognize the benefits of increased cycling, however, rates of bicycling for transport remain low and programming interventions have been limited and rarely rigorously evaluated. We investigate the impact of four cycling mentorship interventions based in non-cycling partner organizations on: cycling behaviour, attitudes towards cycling, and willingness to spend on bicycles and accessories. Residents, mostly newcomers to Canada, participated in 12–16 week cycling mentorship programs, involving personal support from an experienced cyclist. They were provided with safety training, bicycles, locks and helmets and publicly committed to participate in the program. 146 of the 197 participants completed entry and exit surveys. At program exit each participant cycled on average an additional 1.8 days per week to shopping (p ≤ 0.001) and an additional 1.35 days per week to work and school (p ≤ 0.001) compared to program entry. At program exit, participants were willing to spend 23% more on a bicycle and 32% more (p < 0.01) on accessories like carriers, helmets and locks. They were more confident about the rules of the road and were aware of safe streets for riding in their neighbourhood. They were less confident of finding a safe route and more aware of the relative rarity of women cyclists. The programs were effective in increasing cycling for transport regardless of the distance people lived from their respective central business district. These results are promising and suggest that with sufficient support people will bicycle in neighbourhoods throughout the region. Increased availability of cycling infrastructure would likely increase confidence in finding a safe route and improve these results.